2011
DOI: 10.3892/etm.2011.210
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulated Annexin A1 expression in gastrointestinal cancer is associated with cancer invasion and lymph node metastasis

Abstract: Abstract. annexin a1 (anxa1) is a calcium-dependent phospholipid-linked protein, involved in anti-inflammatory effects, regulation of cellular differentiation, proliferation and apoptosis. In the present study, we investigated the expression of anxa1 in gastric and colon cancer, and analyzed the relationship between ANXA1 expression and clinicopathological factors. anxa1 mrna expression in gastric and colon cancer tissues was not significantly changed compared to that in normal tissues. When anxa1 protein expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 23 publications
1
58
1
Order By: Relevance
“…While the ANXA1 expression on cancer tissues is downregulated in head and neck, esophageal and prostate cancer, the expression is upregulated in stomach, colorectal, pancreas and hepatic cancer (12)(13)(14)(15)(16)(17)(18)(19). In breast cancer, the expression and functional roles of ANXA1 are controversial.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the ANXA1 expression on cancer tissues is downregulated in head and neck, esophageal and prostate cancer, the expression is upregulated in stomach, colorectal, pancreas and hepatic cancer (12)(13)(14)(15)(16)(17)(18)(19). In breast cancer, the expression and functional roles of ANXA1 are controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that ANXA1 may promote metastasis formation by enhancing the TGFβ/Smad signaling pathway (27). On the other hand, we previously reported that the expression of ANXA1 is upregulated in gastric and colon cancer and it is involved in cancer invasion as well as lymph node metastasis (16). Here, we investigated the ANXA1 expression in breast cancer and the relationship between ANXA1 expression and clinicopathological features.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ANXA1 also exhibits a low expression in GC and negatively correlates with invasion and metastasis [4] . However, other studies have revealed opposite results [5,6] . We performed laser capture microdissection (LCM) to investigate the relation of ANXA1 expression in GC to the clinical parameters and to obtain purified gastric adenocarcinoma cells (GAC) and normal gastric epithelial cells (NGEC).…”
Section: Introductionmentioning
confidence: 86%
“…We also reported that ANXA1 enhanced breast cancer invasion and metastasis under hypoxia in in vitro cell experiments, indicating that ANXA1 was apparently associated with breast cancer progression 4) . In addition, we stated that colon cancer cases with positive ANXA1 expression by IHC staining were associated with lymphatic invasion (P = 0.011), venous invasion (P = 0.023), and lymph node metastasis (P = 0.042) 5) . The colon cancer cases with positive ANXA1 staining were not statistically associated with poor survival 5) .…”
Section: Introductionmentioning
confidence: 95%